ENHANCE STUDENTS’ READING COMPREHENSION THROUGH DIGITAL STORYTELLING - Donny Adiatmana Ginting; Maitri Ramadhani; Muhammad Hassan; Yusrah Yusrah (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
As we all know, the purpose of teaching students to read short tales is to help them understand the material and analyze the elements of the story, including the moral value, storyline, setting, and characters. The purpose of this study was to determine (1) what the students' initial conditions on reading short story texts were before to using the developed digital storytelling, and (2) how successful the developed digital storytelling utilized for teaching short story reading is. This digital tale was created as a result of the findings of this study, which were based on the results of questionnaires and interviews. It was discovered that the digital storytelling media should cover the needs of the students, which have some criteria such as after reading the short stories, hopefully they can increase their vocabulary, they like to read dramatic and romantic stories, the suitable medias in learning reading of short stories are online reading sources and video, types of digital storytelling are video words and digital storytelling video clips, digital storytelling should be easy to operate an After using digital storytelling to teach short story reading, the students demonstrated this progress. The production of materials improves students' grades and can increase their enthusiasm in reading short stories.